Exercise and training in women, part II: Influence of menstrual cycle and pregnancy - Shephard, R. J. (Canadian Journal of Applied Physiology, 2000)
This part of the review considers the impact of the menstrual cycle and pregnancy upon exercise performance, together with the implications of continued, regular exercise for the developing foetus. Specific issues that are covered include changes in physical performance over the menstrual cycle; the impact of training on the menstrual cycle; a need for awareness of potential pregnancy; alterations in fitness, performance, circulatory, respiratory and metabolic function during pregnancy; potential hazards to the foetus from hyperthermia and hypoxia; a recommended physical activity programme for the pregnant woman; and the impact of continued exercise upon pregnancy outcomes.